2022
DOI: 10.1177/21582440221139469
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perceived Service Quality and Purchase Intention: Two Moderated Mediation Models Investigation

Abstract: This study aims to investigate the relationships of perceived service quality, brand image, customer satisfaction, and purchase intention. The moderated mediating role of brand love is examined on 522 mobile phone consumers in Taiwan. This study found a positive relationship between perceived service quality and purchase intention. Brand image and customer satisfaction play a fully mediated role between perceived service quality and purchase intention. Moderated mediation model one and two found that brand lov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 60 publications
1
6
0
1
Order By: Relevance
“…The qualitative interview results suggest Muslims buy based on religiosity, with the halal label and ingredients being the most critical factors. Finally, the study finds that purchase intention significantly mediates between product attributes, brand trust, customer satisfaction, and religious purchase behavior, consistent with previous literature [ 4 , [44] , [45] , [46] ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The qualitative interview results suggest Muslims buy based on religiosity, with the halal label and ingredients being the most critical factors. Finally, the study finds that purchase intention significantly mediates between product attributes, brand trust, customer satisfaction, and religious purchase behavior, consistent with previous literature [ 4 , [44] , [45] , [46] ].…”
Section: Discussionsupporting
confidence: 89%
“…Based on previous literature and discussions, we have proposed and hypothesized the following conceptual framework, shown in Fig. 1 and derived from the previous studies [ 2 , 4 , 5 , 8 , 9 , 13 , 15 , 18 , 37 , [21] , [22] , [23] , [24] , [33] , [39] , [40] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , 36 , 45 , 46 ].
Fig.
…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…After validating the measurement model, this study used SEM to evaluate the suggested hypotheses. Empirical research regarding BA, culture, SN and behavioural intentions has largely adopted SEM for such investigations (Liao et al 2022;Zayed et al 2022).…”
Section: Evaluation Of the Structural Model And Proposed Hypothesesmentioning
confidence: 99%
“…Selain itu, banyak peneliti telah mengkonfirmasi bahwa service quality mempengaruhi kepuasan pengguna layanan e-government (Abdulkareem & Ramli, 2021;Alhanatleh et al, 2022;A. Alkraiji & Ameen, 2022;Hariguna et al, 2019;Liao et al, 2022;Wang & Liao, 2008). Atas dasar hal tersebut maka kami membangun hipotesis sebagai berikut: H5: Service quality pada e-office berpengaruh positif terhadap use pegawai kementerian H6: Service quality pada e-office berpengaruh positif terhadap satisfaction pegawai kementerian DeLone and McLean (2003) berpendapat bahwa intention to use dan use merupakan alternatif dalam model kesuksesan sistem informasi.…”
unclassified